Design Of An Accounting Recording System Based On Microsoft Access At Putra Solo Petshop - Meily Juliani; Naida Aisyah Alima (ConCEPt - Conference on Community Engagement Project, 2023)
Putra Solo Petshop is one of the businesses engaged in trade and the location of this shop at Ruko Aladin Blok B No 1 Cikitsu, Batam Centre. Putra Solo Petshop has been chosen as a partner in carrying out a Community Service activity. Recording activities carried out by Putra Solo Petshop use a manual accounting recording system, namely by writing all transactions in a book. The recording process is still not neat and clear. This can lead to inefficient and inaccurate recording results. In addition, the existence of transactions that are missed or not recorded by the owner will cause the owner to not clearly know the profit generated. Therefore, the solution that can be done in dealing with these problems is to design an accurate accounting system using the Microsoft Office Access system. The method used in this activity is observation and direct interviews with partners. the results of the interviews that have been conducted, the author can find out some store information and current store conditions. The owner has also approved the author's request to help his business by designing a financial reporting system. The purpose of this community service activity is to design a Microsoft Access system that can produce accurate financial reports. The system that has been created is able to provide all the information that can facilitate business owners in making business decisions.